Encouraging Students to Have Positive Attitudes Toward Learning English - Abdullah Syukur (Ethical Lingua: Journal of Language Teaching and Literature, 2016)
A positive attitude is a powerful tool that fosters enthusiasm, promotes self-esteem, and creates an atmosphere conducive to learning. Achievement in a target language relies not only on intellectual capacity, but also on the learner’s attitudes towards language learning. Attitudes could be viewed as a tendency to respond positively or negatively towards a certain thing, idea, person, situation etc. The attitudes that the students should have are attitude towards the language, attitude towards learning the language, attitude towards the language teacher, and attitude towards school in general. This study focuses on discussing about encouraging students to have positive attitudes toward learning English.